2017
DOI: 10.1001/jamainternmed.2017.1144
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Price Transparency Intervention in the Electronic Health Record on Clinician Ordering of Inpatient Laboratory Tests

Abstract: are considering increasing price transparency at the time of order entry. However, evidence of its impact on clinician ordering behavior is inconsistent and limited to single-site evaluations of shorter duration.OBJECTIVE To test the effect of displaying Medicare allowable fees for inpatient laboratory tests on clinician ordering behavior over 1 year. DESIGN, SETTING, AND PARTICIPANTSThe Pragmatic Randomized Introduction of Cost data through the electronic health record (PRICE) trial was a randomized clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 24 publications
1
73
0
Order By: Relevance
“…Similarly, in a randomized trial of price transparency for inpatient laboratory testing, we found that displaying prices for more expensive tests led to a small though significant decline in test ordering, but it was offset by increases in ordering of less expensive tests. 5 Although displaying prices may intuitively seem like a good idea, many prices may have been lower than clinicians expected (e.g., a basic metabolic panel was $11). Careful evaluation of intended and unintended consequences is essential in optimizing these interventions.…”
mentioning
confidence: 99%
“…Similarly, in a randomized trial of price transparency for inpatient laboratory testing, we found that displaying prices for more expensive tests led to a small though significant decline in test ordering, but it was offset by increases in ordering of less expensive tests. 5 Although displaying prices may intuitively seem like a good idea, many prices may have been lower than clinicians expected (e.g., a basic metabolic panel was $11). Careful evaluation of intended and unintended consequences is essential in optimizing these interventions.…”
mentioning
confidence: 99%
“…Another 6 studies were added from those identified by pearling reference lists for a total of 13 studies [10][11][12][13][14][15][16][17][18][19][20][21]26 for the final analysis. The results constituted 8 randomized controlled trials, 10,12,15,16,18,20,21,26 2 interrupted time series studies, 14,19 2 controlled clinical trials 11,13 and a prospective comparative study. 17 The sequence describing the above process can be found in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…Designs of the studies varied as described above. Randomized studies differed based on level of randomization (Four at the level of test, 15,16,21,26 2 at the level of ordering provider, 18,20 1 at the level of patient 12 and 1 at the level of physician's computer session 10 ) The population and the setting in which the studies were done also varied (Four studies done in a community outpatient setting where providers who completed graduate medical education practiced, 11,14,18,20 9 studies done in hospital and outpatient settings of teaching hospitals 10,12,13,[15][16][17]19,21,26 ) The design of the price display also varied (2 studies displayed cost data, 18,20 2 studies utilized hospital input cost, 17,19 7 studied used charge data 10,12,[14][15][16]21,26 and 2 studies displayed wholesale market price 11,13 )…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations